From Policy to Practice: Measures Against Sexual Abuse by Swedish Sports Federations - Johansson, Susanne (Frontiers in Sports and Active Living, 2022)
The sport movement must protect children and young athletes from all forms of abuse. However, research points to a disconnect between policy and implementation of policy against sexual abuse. No studies have investigated measures against sexual abuse in Swedish sport. The purpose of this study was to explore measures against sexual abuse in the 10 largest sports federations (SFs) for child and youth sport in Sweden. The study draws on interviews with representatives (n = 18) of the SFs and on a review of SFs' website content regarding sexual abuse and safe sport. Results show that the SFs have taken few or no measures against sexual abuse. Measures for safe sports vary in existence, development, and organization between the SFs, and many SFs are in the early stages of safe sport measures and practice. Although the SF representatives emphasize that sexual abuse is unacceptable, a conflict between making it visible or invisible emerges and creates a gap between policy and practice. Reproducing a culture of silence around sexual abuse in sports seems advantageously for SFs. Social and organizational factors that can debilitate safe sport measures and facilitate sexual abuse in sport are discussed.